Six-coordinate oxime-imine cobalt(III) complexes with amino acid co-ligands; synthesis and characterisation (Baghdad Science Journal, 2025)
In this publication, several six coordinate Co(III)-complexes are reported. The reaction of 2,3-butanedione monoxime with ethylenediamine or o-phenylenediamine in mole ratios of 2:1 gave the tetradentate imine-oxime ligands diaminoethane-N,N`-bis(2-butylidine-3-onedioxime) H2L1 and o-phenylenediamine-N,N`-bis(2-butylidine-3-onedioxime), respectively. The reaction of H2L1 and H2L2 with Co(NO3)2, and the amino acid co-ligands (glycine or serine) resulted in the formation of the required complexes. Upon complex formation, the ligands behave as a neutral tetradantate species, while the amino acid co-ligand acts as a monobasic species. The mode of bonding and overall geometry of the complexes were determined through physico-chemical and spectroscopic methods. These studies revealed octahedral geometry about Co(III) complexes in which the co-ligands bound through the amine and the carboxylate groups. Molecular structure for the complexes have been optimised by CS Chem 3D Ultra Molecular Modelling and Analysis Program and supported six coordinate geometry.